(untitled) (Applied Biological Research, 2011)
A potent strain of Bacillus licheniformis was isolated among the various xylanolytic bacteria obtained from agricultural fields of Allahabad (India). The strain produced xylanase in a broad temperature (40-70ºC) and pH (5-11) range with optimum production at 50ºC (for 48 hr) and pH 7.0+0.2. The peak enzyme activity was observed when the substrate was supplemented with xylose, ammonium nitrate and tryptone. A single form xylanase with a low molecular weight (42 kDa) was purified to 3.9-fold with 6.7% recovery rate. Further, the homology modeling of xylanase produced by B. licheniformis was carried out using a template (PDB ID = 1AXK) having sequence similarity of 90% with the query sequence. The reliability of final model confirmed a 92.8% acceptability of Ramachandran plot statistics when validated through PROCHECK and VERIFY 3D. A similar pocket volume obtained from CastP and Pocket Finder were 253 and 268 Å3, respectively. The molecular orientation scored the lowest energy level (-6.24 kcal mol-1) suggesting maximum stability of docked complex. The hydrogen bonding and hydrophobic interactions between ligand and active site lining residues suggested their importance in the catalytic activity and hence this xylanase could be used effectively in industrial applications.